The effect of self-confidence on performance in sports: a meta-analysis and narrative review - Jekauc, D.; Fiedler, J.; Wunsch, K.; Mülberger, L.; Burkart, D.; Kilgus, A.; Fritsch, J. (International Review of Sport and Exercise Psychology, 2025)
Self-confidence refers to the belief that one is capable of performing the actions necessary to overcome difficult situations and succeed in sports. Previous meta-analyses suggest that high self-confidence has a positive effect on sports performance. The main purpose of the present article was to provide an overview of studies assessing this relationship and relevant moderators. A systematic search of five relevant databases was conducted to find studies that measured pre-competition confidence and determined correlations with subsequent performance. Thirty-one studies with 52 samples published between 2002 and 2021 were found. The results suggest that there is a significant linear relationship between self-confidence and performance, with an overall r = 0.30 (95% CI [0.21; 0.37]). There was considerable heterogeneity in the results (Q = 239.1; df = 51; p < 0.01; I2 = 86.5%), with only the performance measure having a significant effect on the effects among the moderators examined. Although hardly any study examined the linearity of the relationship, the large heterogeneity suggests that the relationship is probably at least partially nonlinear. There was some evidence for mechanisms, such as moderating the effects of pressure on performance, influencing other participants in the competition, increased use of coping strategies, and physiological mechanisms.